Chocolate aroma: Factors, importance and analysis. (May 2020) - Toker, Omer Said; Palabiyik, Ibrahim; Pirouzian, Haniyeh Rasouli; Aktar, Tugba; Konar, Nevzat
Abstract: Background: The quality and value of chocolate are related to its unique and fascinating flavor arisen from volatile and non-volatile compounds present in the product. The particular chocolate aroma is dependent on various factors including genotype and the agro-ecological niche (environment conditions, farming practices), post-harvest conditions and complex biochemical and chemical reactions during this period (fermentation, drying) and manufacturing stages. Scope and approach: In this study, relationship between chemical compounds and cocoa flavors, control and management of post-harvest practices and manufacturing processing in order to obtain chocolate with differentiated characteristics and also evaluation methods especially sensory aspects of the chocolate are highlighted. For this purpose, instrumental experiments including headspace aroma extraction, simultaneous distillation extraction and sensory testing such as discrimination experiments, descriptive tests and hedonic experiments were discussed. Key findings and conclusions: A comprehensive link between the components of cocoa flavor, sensory characteristics, human acceptability, and also the processes involved in flavor formation and formulation used, will assist the administration of a traceability system, a challenging case for quality assurance groups. Highlights: Flavor has an important role in the unique taste of chocolate. Fermentation, drying and roasting in cocoa processing have a great influence. Chocolate mass production may affect in formation and removing of some aromatic compounds.